Impact of Asymptomatic Flatfoot on Clinical and Radiographic Outcomes of the Modified Lapidus Procedure in Patients with Hallux Valgus. Issue 4 (November 2022) - Rajan, Lavan; Kim, Jaeyoung; An, Tonya W.; Mizher, Rami; Srikumar, Syian; Fuller, Robert; Cororaton, Agnes D.; Ellis, Scott J.
Category: Midfoot/Forefoot; Bunion Introduction/Purpose: Patients presenting for hallux valgus frequently have an associated flatfoot deformity; however, many are not symptomatic. It is unclear if an asymptomatic flatfoot adversely affects outcomes of hallux valgus correction and should be simultaneously addressed. Prior studies have demonstrated that flatfoot alignment may not affect clinical outcomes after osteotomy procedures, yet no studies have investigated whether this also affects outcomes of the modified Lapidus procedure. The modified Lapidus achieves multiplanar correction through the tarsometatarsal (TMT) joint and stabilizes the medial column, which may be advantageous for flatfoot pathology. We aimed to investigate the relationship between asymptomatic flatfoot and patient-reported and radiographic outcomes after modified Lapidus for hallux valgus. We hypothesized that clinical and radiographic outcomes would be minimally affected by the presence of asymptomatic flatfoot. Methods: This was a retrospective cohort study including 142 patients who underwent the modified Lapidus procedure for hallux valgus at a single institution by 1 of 10 fellowship-trained foot and ankle surgeons. Sixty-one patients met radiographic criteria for asymptomatic flatfoot, which were 1) Meary's angle > 4 degrees, 2) calcaneal pitch < 18 degrees, and talonavicular coverage angle (TNCA) > 7 degrees. Patients with cavus deformity were excluded. Preoperative and minimum 1-year postoperative Patient-Reported Outcomes Measurement Information System (PROMIS) scores between asymptomatic flatfoot and control groups were compared. Radiographic assessment involved comparisons of hallux valgus angle (HVA), intermetatarsal angle (IMA), Meary's angle, talonavicular coverage angle (TNCA), and calcaneal pitch (CP). Preoperative and postoperative radiographic measures were compared to assess improvement in hallux valgus and flatfoot parameters. Results: Preoperatively, the flatfoot group had higher BMI (24.6 vs 22.6, P < .01). Both groups demonstrated preoperative to postoperative improvement in PROMIS physical function (P < .01), pain interference (P < .001), pain intensity (P < .001), and global physical health (P < .001). There were no preoperative or postoperative differences in PROMIS scores between groups (Table 1). Preoperatively, the flatfoot group had a higher IMA (15.2 vs 14.0 degrees, P = .02). Postoperatively, there were no differences in HVA or IMA between groups; however, the flatfoot group exhibited greater deformity in Meary's angle (8.3 vs -0.1 degrees), TNCA (19.2 vs 14.3 degrees), and CP (15.1 vs 19.6 degrees) (all P < .001). Both cohorts demonstrated significant preoperative to postoperative improvement in all radiographic parameters except for CP in the control group (P = .95). Conclusion: There were no significant postoperative differences in patient-reported outcomes of the modified Lapidus procedure between patients with and without asymptomatic flatfoot. Both groups achieved similar excellent radiographic correction of their hallux valgus deformity. Although radiographic flatfoot parameters did not improve to the level of control patients, patients experienced clinical improvement, without adverse outcomes or new flatfoot symptomatology. The modified Lapidus effectively corrects forefoot deformity and concurrently addresses instability at the first TMT joint, making it a valuable option for hallux valgus correction in patients with asymptomatic flatfoot.